In-situ Cr-doped Alumina Nanorods Powder Prepared by Hydrothermal Method. Issue 7 (July 2016) - Xuanmeng, He; Zhenfeng, Zhu; Hui, Liu; Lu, Fu
Abstract: Cr-doped ammonium aluminum carbonate hydroxide nanorods were prepared by a hydrothermal method, with Al(NO3 )3 ·9H2 O, Cr(NO3 )3 ·9H2 O, and urea as raw materials and PEG-20000 as surfactant. In-situ Cr-doped alumina nanorods powder was obtained through calcining its precursors (Cr-doped ammonium carbonate hydroxide nanorods) at 1200 °C. The crystal composition, the structure and the morphology of the as-prepared products were characterized by XRD, SEM and FTIR. Besides, the color performances of the products were analyzed by UV/Vis/NIR spectrometer and automatic color measurement. Results show that the precursors of Cr-doped alumina nanorods powder prepared by the hydrothermal method are composed of uniform nanorods. After its calcinations at 1200 °C, the in-situ doping of Cr in the alumina substrate is achieved. In the Cr-doped alumina nanorods powder, a continuous solid solution of Cr2 O3 and Al2 O3 is formed, which has a corundum crystal structure. With the increasing Cr content, Cr-doped ammonium aluminum carbonate hydroxide nanorods gradually become short, and the melting phenomenon occurs in calcined products. UV-Vis spectroscopy analysis shows that Cr-doped alumina nanorods powder has three strong absorption bands at 562, 406 and 372 nm, thus leading to a pink color for samples which is in agreement with chromatic data. In the present study, Cr-doped alumina nanorods powder prepared by the hydrothermal method can reduce the formation temperature of corundum crystal structures and resolve the problem of mixing homogeneity of Al2 O3 and Cr2 O3, which will contribute to the preparation and the application of alumina-chrome refractory, pink corundum abrasive and ceramic pigment.